Dynamic response of senegal mahogany in the transverse direction under wind loading - Yiek, Mildred Feng Yee (2018)
The number of trees in Singapore has been increasing significantly for the past few years. As a highly populated island nation, the event of tree failure can be rather catastrophic. This research aims to investigate the dynamic response of trees in Singapore under wind loading, in order to eliminate the occurrence of tree failure. This study focuses only on the inter-relationship between fluid dynamic and structural mechanics. The effect of geotechnical mechanisms on the tree stability is not considered in this study. In order to establish the correlation between dynamic response of trees in the transverse direction and wind loading, laboratory tests and results analysis were carried out on a 3D printed tree. The 3D printed tree was modelled based on the measurements of a real Senegal Mahogany (Khaya Senegalensis). The laboratory tests include the measurement of tree trunk transverse displacement and results analysis was conducted using the Fast Fourier Transform Function in Matlab. Results show that there is certain correlation between the dynamic response of trees in the transverse direction and wind loading. The results presented here are limited yet have profound implications for future prediction of tree failure events.